Growth of random polyhedral void in structural steel based on micromechanical RVE simulations. (January 2023) - Xie, Jinbao; Zhang, Rui; Liu, Tao; Zhou, Changfeng; Gu, Tianyu; Chen, Bo; Chen, Yu; Jia, Liang-Jiu
Highlights: RPVs of structural steel identified by in-situ high-resolution μXCT. A microscopic unit cell model containing an RPV established. Effects of aspect ratio and sphericity investigated for RPV growth. Effects of orientation and initial void volume fraction studied for RPV growth. Formulae evaluating RPV growth proposed. Abstract: This paper investigates growth of random polyhedral voids (RPVs) in structural steel, which is a critical stage for ductile fracture of steel. An in-situ high-resolution μXCT experiment shows that most micro-voids in structural steels can be characterized by RPVs. In this study, a micromechanical representative volume element (RVE) model containing an RPV was established with periodic boundary conditions. Comparison of RPV growths with spherical and elliptical void growths was conducted for model validation. On this basis, effects of geometric parameters of the RPV on void growth were analyzed through Python-based parametric modeling in ABAQUS with respect to the aspect ratio, orientation, sphericity, initial void volume fraction, respectively. The results found that growth of the RPV decreases with an increasing initial aspect ratio of the RPV. Growth of the RPV increases as the initial sphericity of RPV decreases. When the initial orientation of RPV tends to be perpendicular to the main tensile direction, a greater void growth will be obtained. The initial volume fraction of RPV has a minor effect on void growth compared with the other geometric parameters. For engineering application, accurate and simplified formulae were proposed to evaluate growth of microscopic RPVs, respectively. Graphical abstract: Image, graphical abstract